The Use of Reactive Programming in the Proposed Model for Cloud Security Controlled by ITSS - Hyseni, Dhuratë; Piraj, Nimete; Çiço, Betim; Shabani, Isak (Computers (Basel), 2022)
Reactive programming is a popular paradigm that has been used as a new solution in our proposed model for security in the cloud. In this context, we have been able to reduce the execution time compared to our previous work for the model proposed in cloud security, where the control of security depending on the ITSS (IT security specialist) of a certain organization based on selecting options. Some of the difficulties we encountered in our previous work while using traditional programming were the coordination of parallel processes and the modification of real-time data. This study provides results for two methods of programming based on the solutions of the proposed model for cloud security, with the first method of traditional programming and the use of reactive programming as the most suitable solution in our case. While taking the measurements in this paper, we used the same algorithms, and we present comparative results between the first and second methods of programming. The results in the paper are presented in tables and graphs, which show that reactive programming in the proposed model for cloud security offers better results compared to traditional programming.